Hokuloa Road - Hand, Elizabeth (Mulholland Books/Little, Brown and Company, 2022)
"On a whim, Grady Kendall applies to work as a live-in caretaker for a luxury property in Hawai'i, as far from his small-town Maine life as he can imagine. Within days he's flying out to an estate on remote Hokuloa Road, where he quickly uncovers a dark side to the island's idyllic reputation: It has long been a place where people vanish without a trace. When a young woman named Jessie from his flight becomes the next to disappear, Grady is determined - and soon desperate - to figure out what happened to her, and to all those staring out of the island's 'missing' posters. But working with Raina, Jessie's fiercely protective best friend, to uncover the truth is anything but easy, and with an inexplicable and sinister presence stalking his every step, Grady can only hope he'll find the answer before it's too late." -- From jacket flap.